UPLC-ESI-MS/MS Profile and Antioxidant, Cytotoxic, Antidiabetic, and Antiobesity Activities of the Aqueous Extracts of Three Different Hibiscus Species - Hanan M. Al-Yousef; Wafaa H. B. Hassan; Sahar Abdelaziz; Musarat Amina; Rasha Adel; May A. El-Sayed (Journal of Chemistry)
The aqueous extracts of Hibiscus calyphyllus (HcA), Hibiscus micranthus (HmA), and Hibiscus deflersii (HdA) growing in Saudi Arabia did not receive enough attention in phytochemical and biological studies. This inspired the authors to investigate the phytochemicals of these extracts for the first time using UPLC-ESI-MS/MS in negative and positive ionization modes. The analysis afforded the tentative identification of 103 compounds including phenolic compounds, flavonoids, and anthocyanins. Moreover, in vitro evaluations of their cytotoxic, antioxidant, antidiabetic, and antiobesity activities were carried out. The results showed that aqueous extract of Hibiscus calyphyllus had the highest activity as an antioxidant agent (SC50 = 111 ± 1.5 μg/mL) compared with ascorbic acid (SC50 = 14.2 ± 0.5 μg/mL). MTT assay was used to evaluate cytotoxic activity compared to cisplatin. Hibiscus deflersii showed the most potent cytotoxic effect against A-549 (human lung carcinoma) with IC50 = 50 ± 5.1 μg/mL, and Hibiscus micranthus showed a close effect with IC50 = 60.4 ± 1.7 μg/mL. Hibiscus micranthus showed the most potent effect on HCT-116 (human colon carcinoma) with IC50 = 56 ± 1.9 μg/mL compared with cisplatin (IC50 = 7.53 ± 3.8 μg/mL). HcA and HdA extracts showed weak cytotoxic activity against A-549 and HCT-116 cell lines compared to the other extracts. Eventually, Hibiscus deflersii showed astonishing antidiabetic (IC50 = 56 ± 1.9 μg/mL) and antiobesity (IC50 = 95.45 ± 1.9 μg/mL) activities using in vitro α-amylase inhibitory assay (compared with acarbose (IC50 = 34.71 ± 0.7 μg/mL)) and pancreatic lipase inhibitory assay (compared with orlistat (IC50 = 23.8 ± 0.7 μg/mL)), respectively. In conclusion, these findings are regarded as the first vision of the phytochemical constituents and biological activities of different Hibiscus aqueous extracts. Hibiscus deflersii aqueous extract might be a hopeful origin of functional constituents with anticancer (on A-549 cell line), antidiabetic, and antiobesity activities. It might be a natural alternative remedy and nutritional policy for diabetes and obesity treatment without negative side effects. Isolation of the bioactive phytochemicals from the aqueous extracts of aerial parts of Hibiscus calyphyllus, Hibiscus micranthus, and Hibiscus deflersii and estimation of their biological effects are recommended in further studies.